The impact of village savings and lendings on rural livelihoods: a case of Vheneka village: Chipinge district - Zimunya, Anesu Abel (Midlands State University, 2017)
Village savings and lending associations have become a strength to consider in regards to the reduction of worldwide rural poverty. The popular proposition is that by enabling poor rural households access to loans and other microfinance services, the rural populace can then embark on income generating activities which will help them in dealing with numerous adversities that the rural populace face such as unemployment, lack of access to health services, low household food consumption and high levels of poverty. The chief research objective of this dissertation was to examine the impact of village savings and lending associations on rural livelihoods in Vheneka village. The study is an investigational case of VSLA members in the Vheneka community in Chipinge district and using qualitative methodology the study revealed that the VSLAs have made an impact on the rural livelihood of the Vheneka community. Improved food security, access to health services, an increment in employment rate, increment in durable assets, improved household income and the presence of income generating activities are testimony to the impact that the VSLAs have made on rural livelihoods in Vheneka community. Limitations that were noticed in relation to VSLAs are the issue of loan repayment, VSLAs lack of playing a role in mind set change of non –VSLA members, VSLA’s lack of integration with other rural livelihood intervention and recommendations were given.